Analisis Produk Not Good (NG) dalam Proses Pemotongan Kardus dengan Metode Failure Mode and Effects Analysis (FMEA) - Al Fahri, Dzalfa Difa; Sukanta, Sukanta; Nugraha, Asep Erik (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
PT BCD is a company engaged in the manufacturing sector, specifically in the manufacture of packaging made from cardboard. In the production process, there is cardboard cutting using a cutting machine to cut cardboard with predetermined quality standards such as producing products that are not defective or Not Good (NG) products. The presence of NG products in January. With this problem, it is necessary to identify the slitter machine by applying the FMEA method to identify the problems that occur. The purpose of the study is to carry out quality control to reduce the occurrence of NG products produced by the slitter machine. In January, it was found that there were 528 NG products. Researchers used Failure Mode and Effects Analysis to find the root cause of the problem. The variables contained in the RPN are Severity, Occurrence, Detection. Judging from the Failure Mode and Effects Analysis (FMEA) method approach, the cause of the occurrence of Not Good (NG) products is the result of untidy cutting according to the highest RPN value with a value of 224, namely a blunt knife. Keywords: FMEA, Product Not Good, Quality Control